Unravelling the full relaxation dynamics of superexcited helium nanodroplets. Issue 28 (13th July 2021) - Asmussen, Jakob D.; Michiels, Rupert; Dulitz, Katrin; Ngai, Aaron; Bangert, Ulrich; Barranco, Manuel; Binz, Marcel; Bruder, Lukas; Danailov, Miltcho; Di Fraia, Michele; Eloranta, Jussi; Feifel, Raimund; et al.
Abstract : The relaxation dynamics of superexcited superfluid He nanodroplets is thoroughly investigated by means of extreme-ultraviolet (XUV) femtosecond electron and ion spectroscopy complemented by time-dependent density functional theory (TDDFT). Abstract : The relaxation dynamics of superexcited superfluid He nanodroplets is thoroughly investigated by means of extreme-ultraviolet (XUV) femtosecond electron and ion spectroscopy complemented by time-dependent density functional theory (TDDFT). Three main paths leading to the emission of electrons and ions are identified: droplet autoionization, pump–probe photoionization, and autoionization induced by re-excitation of droplets relaxing into levels below the droplet ionization threshold. The most abundant product ions are He2 +, generated by droplet autoionization and by photoionization of droplet-bound excited He atoms. He + appear with some pump–probe delay as a result of the ejection He atoms in their lowest excited states from the droplets. The state-resolved time-dependent photoelectron spectra reveal that intermediate excited states of the droplets are populated in the course of the relaxation, terminating in the lowest-lying metastable singlet and triplet He atomic states. The slightly faster relaxation of the triplet state compared to the singlet state is in agreement with the simulation showing faster formation of a bubble around a He atom in the triplet state.